PENGARUH PENERAPAN MODEL PEMBELAJARAN TALKING STICK DISERTAI EVERYONE IS A TEACHER HERE TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP NEGERI 3 SIJUNJUNG TAHUN PELAJARAN 2013/2014 - Ariani, Wiga; Rahmi, Rahmi; Rahima, Rahima (STKIP PGRI Sumbar, 2013)
This research is based on understanding of mathematical concept and the lack of individual studentâs responsibility. It refers to the result 8th grade from SMP N 3 Sijunjung, Year of study 2013/2014. The purpose of this research is to know understanding of student mathematical concept that apply âtalking stickâ with âeveryone is a teacher hereâ is better than understanding concept of mathematical that apply conventional learning at class VIII SMP N 3 Sijunjung. This kind of research is experimental type, subject is selected randomly. This research populution is student of VIII SMP N 3 Sijunjung, year of study 2013/2014 which is consisted of five classes. to definite experiment class and control class is executed randomly. Thatâs how class VIII.C chosen as experiment class and VIII.B as control class. Instrumen used in this research is about understanding of mathematical concept. Type of test used is essay with test of realibility 0,718. Analysis technic used is T-test one side with MINITAB software. Based on analysis result is recognized that both class sample have normal distribution and homogeneous. Result of test is recognized as P-value < Î±, so hypotheses for this research is accepted. it can be concluded that understanding of student mathematical concept that apply learning model âtalking stickâ with âeveryone is a teacher hereâ is better than understanding concept of mathematical that apply conventional learning at class VIII SMP N 3 Sijunjung